The mentality and its influence on the legal culture (Journal of actual problems of jurisprudence, 2019)
In this article the concept, types and nature of mentality. The article also discusses the relation of the mentalityand the legal mentality, the legal mentality and legal culture, the impact on the mentality of the legal culture.Keywords: culture, mentality, legal culture, the state, the legal mentality.